2017
DOI: 10.1016/j.desal.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

On the present and future economic viability of stand-alone pressure-retarded osmosis

Abstract: Pressure-retarded osmosis is a renewable method of power production from salinity gradients which has generated significant academic and commercial interest but, to date, has not been successfully implemented on a large scale. In this work, we investigate lower bound cost scenarios for power generation with PRO to evaluate its economic viability. We build a comprehensive economic model for PRO with assumptions that minimize the cost of power production, thereby conclusively identifying the operating conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…In South Korea, PRO was integrated with RO and membrane distillation (MD) systems to process the brine at even higher salinity. These leading pilot plants and recent studies on PRO ( [3,4]) suggest that the most popular salinity pairing of seawater and river water is not feasible and that a more saline draw stream is necessary to make PRO viable. Although these studies identified the need for high salinity, the power density needed for economic viability remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, PRO was integrated with RO and membrane distillation (MD) systems to process the brine at even higher salinity. These leading pilot plants and recent studies on PRO ( [3,4]) suggest that the most popular salinity pairing of seawater and river water is not feasible and that a more saline draw stream is necessary to make PRO viable. Although these studies identified the need for high salinity, the power density needed for economic viability remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This trend suggests that large minimum flux values can be used without significant energetic penalty. Because capital expenditure (CapEx) is the dominant cost factor for PRO [48], increasing the minimum flux (or decreasing the system size) can be an effective way to reduce the overall cost. Ultimately, the savings from operating expenditure (OpEx) in the form of energy reduction should be compared to the additional CapEx of the PRO unit to determine the economic viability of coupling PRO to a desalination system.…”
Section: Pressure-retarded Osmosismentioning
confidence: 99%
“…The local reverse salt flux and the water flux at any axial location (x) can be calculated using Eqs. (24) and (25), respectively [48]:…”
Section: Pressure-retarded Osmosismentioning
confidence: 99%
See 2 more Smart Citations